CENTRAL BANKS AND FINANCIAL STABILITY: GLOBAL EXPERIENCES IN THE POSTPANDEMIC PERIOD - Bozorov Saidjon Hamidovich; Dr. Navik Istikomah, S.E., M.Si. (Innovation Science and Technology, 2025)
The pandemic period posed an unprecedented challenge to the global fnancial system. In response, central banks swiftly implemented monetary easing measures drastically reducing key policy rates and launching liquidity provision programs to avert a systemic crisis. This article analyzes central bank policies and issues related to fnancial stability in the post-pandemic era, focusing specifcally on the refnancing (key) interest rate as a principal policy tool. Drawing on a comparative analysis of experiences in emerging economies such as India, Indonesia, Brazil, South Africa, and Türkiye, the article examines how changes in the key policy rate aﬀect inﬂation, exchange rates, and fnancial stability. The discussion is supported by statistical data and graphical illustrations. Concluding remarks are framed in the context of Uzbekistan, oﬀering practical recommendations aimed at strengthening fnancial stability in the country.